2014
DOI: 10.1182/blood-2014-02-555128
|View full text |Cite
|
Sign up to set email alerts
|

Autologous apoptotic cells preceding transplantation enhance survival in lethal murine graft-versus-host models

Abstract: Key Points• Prophylactic ECP protects against GVHD in a murine BMT model.• ECP provides apoptotic signals that promote tolerance through dendritic cells and Tregs.Acute graft-versus-host disease (GVHD) is induced by alloreactivity of donor T cells toward host antigens presented on antigen-presenting cells (APCs). Apoptotic cells are capable of inducing tolerance by altering APC maturation. Apoptosis can be induced by extracorporeal photopheresis (ECP). We demonstrate that the use of ECP as a prophylaxis prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 55 publications
(62 reference statements)
2
34
0
Order By: Relevance
“…Supporting this concept are data from a murine nonmyeloablative allogeneic bone marrow transplant study that showed that autologous MSCs infusion enhanced long-term engraftment and tolerance [17], whereas infusion of allogeneic MSCs lead graft failure. Data by Florek et al [52] also showed that infusion of apoptotic autologous splenocytes 24 hours before conditioning could delay the onset of GVHD in a murine model. Whether autologous human MSCs for GVHD can induce anergy is unproven; however, it does offer an attractive secondary mechanism by which tolerance may be established and can be tested clinically.…”
Section: Discussionmentioning
confidence: 90%
“…Supporting this concept are data from a murine nonmyeloablative allogeneic bone marrow transplant study that showed that autologous MSCs infusion enhanced long-term engraftment and tolerance [17], whereas infusion of allogeneic MSCs lead graft failure. Data by Florek et al [52] also showed that infusion of apoptotic autologous splenocytes 24 hours before conditioning could delay the onset of GVHD in a murine model. Whether autologous human MSCs for GVHD can induce anergy is unproven; however, it does offer an attractive secondary mechanism by which tolerance may be established and can be tested clinically.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to direct IL-10 inhibition in ECP-treated PBMC, many studies have demonstrated elevated IL-10 either in ECP-untreated DC/ monocytes being cocultured with ECP-exposed cells (12,49,50) or in ECP Tregs, and the requirement for IL-10 was demonstrated in IL-10-deficient mice (10). Furthermore, additional data have suggested that ECP promoted Treg expansion in recipients (51,52). In our view, these results support the hypothesis that ECP may have dual immunomodulatory activity: immunoregulatory activity of ECP-treated apoptotic lymphocytes interacting with ECP-unexposed host cells and possible immunostimulatory activity of directly ECP-exposed monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ECP possibly induces Tregs through incompletely elucidated mechanisms involving the induction of apoptotic cells. 53 Such a role in the induction of Bregs has not been demonstrated to date, although BAFF levels have been linked to the response of cGVHD to ECP. 54 A validation in a higher number of patients would be of interest.…”
Section: Discussionmentioning
confidence: 99%